Land Values, Property Rights, and Home Ownership : Implications for Property Taxation in Peru - Hawley, Zackary; Miranda, Juan José; Sawyer, W. Charles (Elsevier, 2018)
This paper evaluates the effect of property rights on property values in Peru. Previous research on squatting has shed light on how the provision of formal land titles affects a number of socioeconomic outcomes and a subset of this research has provided estimates on how the provision of formal titles affects property values. However, the phenomenon of squatting encompasses a variety of informal property rights distinct from the possession of a legal title. Using an exceptionally rich household data set including geo-location at the community level we study the effects of both formal and informal property rights on property values. Having a title increases property values by almost 7 percent and squatting on the land by invasion reduces values by about 6 percent. Using these estimates, we determine the potential losses of property tax revenue and are able to study the issue of squatting in the context of public finance.